2005
DOI: 10.1007/s10661-005-5309-y
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and Dissipation of Readymix Formulations of Insecticides In/On Okra Fruits

Abstract: Dissipation behaviour of ready mix polytrin C 44EC (profenophos 40% + cypermethrin 4%) and spark 36EC (triazophos 35% + deltamethrin 1%) applied at 1 L/ha in okra crop during Kharif in year 2000 was studied at 0, 1, 3, 5 and 7 days after treatment. Dissipation on 7th day was found to be maximum (98.4%) for profenophos followed by triazophos (86.2%), cypermethrin (73.5%) and deltamethrin (55.7%). Half life (t1/2) values for the above insecticides were 1.35, 2.55, 4.11 and 7.60 days, respectively. All the insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
4
11
0
Order By: Relevance
“…5). Dissipation behavior of cypermethrin in premix formulation Polytrin-C on okra crop has been studied earlier Nath et al 2005). They have reported the half-life of 3.95-4.11 days for cypermethrin which is comparable to the half-life values of 2.0-4.8 days observed in this study with Roket 44EC and Action-505EC formulations.…”
Section: Action-505supporting
confidence: 83%
See 1 more Smart Citation
“…5). Dissipation behavior of cypermethrin in premix formulation Polytrin-C on okra crop has been studied earlier Nath et al 2005). They have reported the half-life of 3.95-4.11 days for cypermethrin which is comparable to the half-life values of 2.0-4.8 days observed in this study with Roket 44EC and Action-505EC formulations.…”
Section: Action-505supporting
confidence: 83%
“…Profenofos residues dissipated with the half-life of 2.2-5.4 days. The half-life values of 1.35 days on okra using pre-mix formulation Polytrin-C Nath et al 2005), 1.84, 1.74, and 1.96 days from hot pepper, sweet pepper, and eggplant (Radwan et al 2005) have been reported earlier. Chlorpyriphos residues on tomato dissipated with the half-life of 2.9-3.3 days.…”
Section: Action-505supporting
confidence: 58%
“…It is an abstemiously poisonous, broad spectrum, non systemic contact OPs, insecticide, and acaricide with nematicidal properties (10,11). Since the late 1970s it has been used in agronomy practices for a number of crops such as vegetables, fruits, cotton, maize, paddy, wheat, and cereals to control aphids, fruit borers, bollworms, red spiders, leaf hoppers and cutworms (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…The concentrated samples were transferred to a flask, and APEM was added to achieve a volume of 5 ml for the GC analysis. The GC analysis used a combination of published methods [5,8]. The triazophos residues were estimated using a GC machine (Model HP-5890 II) equipped with a SGE BPX50 column (50% phenyl equivalent polysilphenylene-siloxane; 30 m  0.53 mm i.d  0.5-lm film thickness).…”
Section: Quantification Of Triazophos Residues In the Different Rice mentioning
confidence: 99%
“…It is used to control aphids, bollworms, red spiders, fruit borers, leaf hoppers and cutworms on a variety of crops and is particularly effective in the control of plant nematodes [3][4][5][6][7][8]. The brown planthopper (BPH), Nilaparvata lugens Stål (Hemiptera: Delphacidae), is a major insect pest of rice in Asia.…”
Section: Introductionmentioning
confidence: 99%